EXPLORING THE PERSPECTIVES OF MUSLIM PATIENTS WITH DIABETES AT ZAMBOANGA CITY MEDICAL CENTER ON MANAGING DIABETES DURING RAMADAN:: A FOCUS GROUP DISCUSSION STUDY ON KNOWLEDGE, ATTITUDES, AND PRACTICES - Sali, Mohammad Elshad (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION For Muslims, fasting during Ramadan is based on a multitude of spiritual benefits; hence, there is an intense desire to participate in the month-long fasting even for those who could seek exemption. In the Philippines, managing diabetes during Ramadan poses unique challenges due to the limited medical evidence available. The study seeks to set up a demographic profile of patients with diabetes who observe fasting during Ramadan and provide substantial data for further research. The study aims to evaluate the knowledge, explore the practices and experiences, and understand attitudes regarding medication, risk, and dietary modifications of Muslim patients with diabetes who are fasting during the month of Ramadan. METHODOLOGY An initial survey was conducted among adult Muslim patients with type 2 diabetes who fasted the previous year. These patients were recruited for the focus group discussion (FGD) via purposive sampling. Focus group discussions were conducted until no new information was obtained, resulting in a total of four group discussions. Descriptive statistics was employed to present clinical and demographic data, while data from the FGDs were subjected to coding and thematic analysis. RESULTS The participants, who had type 2 diabetes and were mostly at high or very high risk, used oral antihyperglycemic agents (OHAs) and fasted for a significant number of days during Ramadan. Complications associated with hypoglycemia and hyperglycemia were reported, which may have been underestimated due to limited monitoring. Thus, interventions including improved monitoring practices must be established for individuals with diabetes when fasting during Ramadan. The challenges that the participants experienced included diet and insulin management, blood sugar control, and exercise disruptions. Strategies that they employed were monitoring, planning, informed food choices, and consultation with doctors. The healthcare professionals play a vital role in providing support, education, and guidance to address concerns and preferences. CONCLUSION The study assessed the knowledge and attitudes of Muslim patients with diabetes regarding diabetes management during Ramadan, revealing varying levels of understanding and diverse attitudes toward fasting. The findings of the research highlight the need for advice, support, closer monitoring, and medication adjustments of Muslim patients with diabetes. Challenges included maintaining medication and diet, blood sugar control, hydration, and exercise disruptions. Facilitators comprised of support systems, healthcare consultations, educational resources, and adherence to meal plans. Tailored interventions, cultural sensitivity, increased support systems, patient education, proactive measures, consistent monitoring, and medical advice are necessary for effective diabetes management during Ramadan. Communication with healthcare professionals and access to comprehensive information and monitoring devices are recommended for effective support.